Integrating Ethnoscience on Critical-Thinking Oriented Web-Based E-Module of Secondary School Science - Monica Prima Sari; Arief Muttaqiin; Rahmah Evita Putri; Rani Oktavia (Postgraduate, University of Mataram, 2024)
As a strategy to create learning environment by integrating culture into learning, ethnoscience fits perfectly with the aims of science lesson in the national curriculum of education in Indonesia, which is to understand how nature works, and to improve awareness toward conserving and maintaining balance in nature. Leading toward Education for Sustainability Development (ESD), science learning could serve to develop students’ ability in thinking, learning, and building awareness towards natural and physical environment. In this study, we aimed to design a web-based e-module integrated with both ethnoscience and critical thinking orientation to facilitate students’ learning dan thinking. The product is developed with 4D-model consisting of 4 stages namely: Define, Design, Develop, and Disseminate. Product’s validity and practicality was assessed using instruments with Likert—scale items and analyzed with descriptive statistics. From Define and Design stage, four themes of ethnoscience are embedded in the e-module, namely: gold panning, salt farming, the making of virgin coconut oil, and Jamu– a folk drink. From develop and disseminate stage, the web-based e-module was tested to be highly valid and practical to be used as teaching materials. The product received positive feedbacks students especially related to the implementation of Kurikulum Merdeka.